Analisis Pengaruh Information Quality Terhadap Re-Purchase Intention - Rudi (Journal Research of Economic and Bussiness, 2025)
This study was conducted to explore the influence of information quality on repurchase intention on the Traveloka app. The data collection method used was a questionnaire. The sample selection procedure used non-probability sampling and purposive sampling by distributing questionnaires to respondents. Based on the results of the data analysis, it shows that the information quality variable has a significant impact on repurchase intention on the Traveloka app. The research findings explain that repurchase intention can be increased by improving information quality, which is a determining factor in successfully increasing repurchase intention